The impact of network positions in scientific collaboration on pharmaceutical firms' technological innovation performance: Moderating roles of scientific collaboration strength and patent stock - Wang, Xing-Xiu; Jiao, Hui-Ying (Frontiers in Public Health, 2022)
Scientific knowledge is important to technological innovation in the pharmaceutical industry. Collaboration is the main way to participate in the creation of scientific knowledge for pharmaceutical firms, so will positions occupied by pharmaceutical firms in the scientific collaboration network affect the performance of technological innovation? Moreover, what factors moderate the scientific collaboration network positions and technological innovation link? Using a dataset based on 194 Chinese publicly traded pharmaceutical companies, this paper constructs the dynamic scientific collaboration networks among 1826 organizations by analyzing 4092 papers included in CNKI and Web of Science databases and then probes the impact and its boundaries of positions in the scientific collaboration network of pharmaceutical firms on the technological innovation performance by negative binomial modeling approach. Our study confirms that degree centrality has an inverted U-shaped impact on pharmaceutical firms’ technological innovation performance, while structural holes play positive roles in promoting pharmaceutical firms’ technological innovation. Moreover, this article identifies that the strength of scientific collaboration positively moderates the U-shaped relationship between degree centrality and technological innovation of pharmaceutical firms, the matching of high patent stock and high structural holes can promote their technological innovation performance. The results deepen the present understanding of scientific collaboration in the pharmaceutical industry and offer new insights for the formulation of pharmaceutical firms’ scientific collaboration strategies.